OPTIMASI SINTESIS DAN KARAKTERISASI SABUN CAIR DARI KEMIRI (Aleurites moluccana) DENGAN BANTUAN GELOMBANG ULTRASONIC - Aman Santoso Santoso; Syafiuddin Syafiuddin; Dedek Sukarianingsih; Sumari Sumari; Rini Retnosari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Liquid soap has become a basic necessity, especially during the Covid pandemic. The quality of soap is influenced by the type of raw material used. Candlenut oil saponification with potassium hydroxide produces liquid soap which has the potential to be anti-bacterial. Ultrasonic waves (US) produce cavitation which speeds up the reaction. This study aims: (1) Synthesis and characterization of liquid hazelnut oil soap, (2) to determine the antibacterial activity of liquid soap. The stages in this study were: (1) isolation and characterization of hazelnut oil, (2) making liquid soap at various alkaline concentrations with US (3) characterizing liquid soap (4) testing for antibacterial activity. The results showed that liquid soap can be made by saponification with KOH hazelnut oil, obtained physical properties of viscous liquid form, yellowish white color, distinctive aroma. The chemical properties of liquid soap have a pH of 8.46, a density of 1.10 g/mL, a free fatty acid content of 0.34%, a free alkaline content of 0.05%, a viscosity of 1,460 cSt and a surface tension of 4.33 x 10-4 N/m. Candlenut liquid soap has antibacterial activity in the weak category against E. coli bacteria and in the moderate category against S. aureus bacteria